The Power of Vision and Mission Statements: A Study on Their Impact on Micro Business Enterprises in Camarines Norte, Philippines - Abin, Genelyn; Llorca, Rosemarie; Sale, Sherlyn G.; Ramirez, Crisanto S. (Jurnal Genesis Indonesia, 2024)
This study explores the vision and mission statements of microbusinesses in Daet, Camarines Norte, focusing on their prevalence, clarity, alignment, impact, obstacles, and challenges. Employing a descriptive quantitative approach, data was collected through a survey questionnaire. Statistical techniques such as weighted mean, frequency, and percentage were utilized, with thirty respondents selected from ten microbusiness industries through descriptive and quota samplings. Findings reveal a prevalent lack of clear vision and mission statements among microbusiness owners, attributed to uncertainty and a perceived low priority. Insufficient skills and resources further hinder the crafting of compelling statements, impacting the success of these enterprises. The study underscores the importance of workshops, training sessions, and seminars to equip microbusiness owners with the necessary tools for developing purposeful vision and mission statements, vital for guiding their business towards success.